The Analysis of Students Health Behavior Factors in an Effort to Prevent Covid-19 - Novita Surya Putri; Annisa Nur Nazmi (Alta Dharma Publisher, 2021)
China and all societies are required to understand and practice the steps for self-protection and of prevention of infection transmission to others. Strategies to prevent Covid-19 infection can be applied by self-isolation or quarantine, promoting public health behaviors, such as: washing hands with soap or hand sanitizer, applying proper cough and sneezing ethics, and maintaining social distancing. This study aimed to determine the factors that influence Covid-19 prevention behavior among students in Banyuwangi Regency, East Java, Indonesia. This study was an observational analytic study and used a cross-sectional design. The sampling used purposive sampling; respondents who returned the online questionnaire were 138 people. Pearson chi square test was conducted to determine the correlation among the variables of gender, age, type of college and knowledge. The results of Pearson chi square test showed that there was an effect between type of college (p = 0,000) and knowledge (p = 0,000) in the efforts to handle, prevent, and care for Covid-19 patients. From the results of multivariate analysis, knowledge was the most influential (r = 0.721; CI = 3.466 - 7,680), which means that knowledge has an effect of 72.1% on student health behavior in efforts to prevent Covid-19. The role of governments and the dissemination of relevant information on social media will influence knowledge on health behavior.